Teaching Numeracy and Science in Early Childhood Education - Huseyn, Nazrin; Allahverdiyeva, Afsana (ADA University, 2023)
Every year, thousands of children are enrolled in different preschool institutions in Azerbaijan. Preschool education has a significant impact in the development of children including their cognitive, behavioral, social-emotional and physical development. At the same time, teaching methodology of pre-school educators is important for the learning of children. This study explores perceptions of preschool educators in teaching numeracy and science in Early Childhood Education and challenges they are facing during the teaching process. Meanwhile, support mechanisms by preschool principals are identified in this paper based on the interviews with principals of different public kindergartens. Ultimately, quantitative and qualitative data collection was conducted with preschool educators and principals of kindergartens to reveal the factors that create the challenges for teachers in teaching numeracy and science and the support provided for those teachers in order to overcome them. The findings highlighted that teachers use various methods and tools while teaching numeracy and science in kindergartens. They teach the basic concepts of numeracy and science through entertainment, integration with other subjects, and individual approach to each child. Meanwhile, the findings revealed that preschool educators face some challenges while teaching numeracy and science in kindergartens. Inappropriate methodology, lack of resources, and insufficient knowledge on the new curriculum create drawbacks for teachers in numeracy and science classes. Additionally, support that principal would provide are organization of regular consultations, trainings and seminars to enrich the knowledge of teachers and help them in overcoming their difficulties. Considering the needs and challenges of pre-school teachers, a Practical Handbook is developed based on the content of the national curriculum and best practices of other countries in order to provide further support for pre-school educators in teaching early numeracy and science.
Keywords: Early childhood education -- Azerbaijan; Numeracy -- Study and teaching (Preschool); Science -- Study and teaching (Preschool); Education